PENGARUH KOMITMEN ORGANISASI DAN PERAN MANAJER PENGELOLA KEUANGAN DAERAH TERHADAP KINERJA MANAJERIAL SATUAN KERJA PERANGKAT DAERAH DI KOTA MANADO - Pandelaki, Leydi; Poputra, Agus T. (Universitas Sam Ratulangi, 2013)
Implementation of performance-based budgeting in government agencies in Indonesia, proclaimed through the enactment of Law No. 17 Year 2003 on State Finance and implemented in stages beginning in the budget 2005.Reformasi financial management resulted in a fundamental change in the financial management of the country / region. The research was conducted at the Regional Working Units Manado City Government. The study population was an employee who worked in Manado City Government on education. Samples were three and four echelons as the authorized users of government budget on education in the city of Manado. Officials in the city of Manado worked as secretary department / agency, department secretary, the head section, sub-section chief, the head of the field, sub-field head and section head who is considered able to describe the performance of each regional secretaries, departments and institutions as a whole technical area . This study aimed to determine the effect of organizational commitment and the role of manager of financial management on the performance of managerial work unit. Collecting data using primary data collection, namely the questionnaire by using purposive sampling technique. Samples were obtained from three-and four-echelon employees who work in regional work units Manado City Government who has served as secretary of the department / agency, the head section, sub-section chief, the head of the field, sub-field head and section head. Data analysis using SPSS software with five stages.First, descriptive statistics.The second phase, testing the quality of the data.The third phase, to test the assumptions of classical aberrations.The fourth stage, performing multiple regression analysis.And fifth stages, testing the hypothesis. The results showed that organizational commitment and significant positive effect on the performance of managerial work unit. While the role of manager of financial management has no effect and no significant effect on work unit performance.